2022
DOI: 10.2478/azibna-2022-0013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with herbal extract as methionine replacer on growth performance, meat composition, oxidative stability and liver gene expression in broiler chickens

Abstract: In the present study, an herbal feed additive was tested for partial-to-complete replacement of synthetic methionine in poultry diets, along with its effects on performance, breast and thigh meat chemical composition, oxidative stability during refrigerated storage and the expression of five target genes in liver. In a 35 days trial, 600 one-day-old male chicks were randomly allocated to 4 groups with 10 replicates. Birds in the control group were fed a regular maize–soybean-based diet that covered DL-methioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Despite numerous investigations into the impact of nutrient-deficient diets on chicken growth, the research on liver gene expression related to enzymes involved in methionine cycle synthesis remains notably lacking, both in farm animals and poultry. In a previous study [47], it was shown that specific extracts of Indian herbs such as Boerhavia diffusa, Azadirachta indica, Vigna mungo, and Trigonella foenum-graecum can affect gene expression and modulate the growth performance of chickens, even when they are given diets with limited quantities of methionine. It is possible that animal feed containing plant extracts rich in active phenolic ingredients possesses the capability for metabolic, physiologic, and growth promoting properties, resulting in a decrease in humoral and cellular responses and associated gene expressions in broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite numerous investigations into the impact of nutrient-deficient diets on chicken growth, the research on liver gene expression related to enzymes involved in methionine cycle synthesis remains notably lacking, both in farm animals and poultry. In a previous study [47], it was shown that specific extracts of Indian herbs such as Boerhavia diffusa, Azadirachta indica, Vigna mungo, and Trigonella foenum-graecum can affect gene expression and modulate the growth performance of chickens, even when they are given diets with limited quantities of methionine. It is possible that animal feed containing plant extracts rich in active phenolic ingredients possesses the capability for metabolic, physiologic, and growth promoting properties, resulting in a decrease in humoral and cellular responses and associated gene expressions in broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, gaining insights into the molecular mechanisms that govern the expression of genes related to amino acid metabolism could provide valuable information for optimizing dietary requirements [83]. It is clear that diet supplementation with extracts from aromatic plants may interfere with the gene expression of amino acid in the synthesis of methionine, and, as a consequence, with protein synthesis [47]. Chickens' diets deficient in methionine have been shown to upregulate the gene expression related to the CAT1 amino acid transporter in large skeletal muscles [83].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation